Al-Muḥarrar Al-Wajīz fī Tafsīr Al-Kitāb Al-‘Azīz Karya Ibnu ‘Aṭiyah - Damanhuri Basyir (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
The works of classical Muslim commentators have to some extent provided us with information about the extensive development of knowledge during that era. Hence, their significant works also serve as studies for the present time and yield further works in modern times. Among the exegesis books from the classical era is the book al-Muḥarrar al-Wajīz fī Tafsīr al-Kitāb al-‘Azīz by Ibn ‘Aṭiyah. The emergence of this interpretation occurred during the zenith of Islam, and its author hailed from the Western world, Spain. The issue at hand in this discussion is the approach to interpreting the book of interpretation al-Muḥarrar al-Wajīz fī Tafsīr al-Kitāb al-‘Azīz, and through this study, the profile and characteristics of this book are expected to be delineated, thus revealing its differences and uniqueness compared to other exegesis books.